The effect of stellar feedback on the formation and evolution of gas and dust tori in AGN - Schartmann, M.; Meisenheimer, K.; Klahr, H.; Camenzind, M.; Wolf, S.; Henning, Th (Monthly notices of the Royal Astronomical Society, 2009)
Recently, the existence of geometrically thick dust structures in active galactic nuclei (AGN) has been directly proven with the help of interferometric methods in the mid-infrared. The observations are consistent with a two-component model made up of a geometrically thin and warm central disc, surrounded by a colder, fluffy torus component. Within the framework of an exploratory study, we investigate one possible physical mechanism, which could produce such a structure, namely the effect of stellar feedback from a young nuclear star cluster on the interstellar medium in centres of AGN. The model is realized by numerical simulations with the help of the hydrodynamics code tramp. We follow the evolution of the interstellar medium by taking discrete mass-loss and energy ejection due to stellar processes, as well as optically thin radiative cooling into account. In a post-processing step, we calculate observable quantities like spectral energy distributions (SEDs) and surface brightness distributions with the help of the radiative transfer code mc3d. The interplay between injection of mass, supernova explosions and radiative cooling leads to a two-component structure made up of a cold geometrically thin, but optically thick and very turbulent disc residing in the vicinity of the angular momentum barrier, surrounded by a filamentary structure. The latter consists of cold long radial filaments flowing towards the disc and a hot tenuous medium in between, which shows both inwards and outwards directed motions. With the help of this modelling, we are able to reproduce the range of observed neutral hydrogen column densities of a sample of Seyfert galaxies as well as the relation between them and the strength of the silicate 10 μm spectral feature. Despite being quite crude, our mean Seyfert galaxy model is even able to describe the SEDs of two intermediate type Seyfert galaxies observed with the Spitzer Space Telescope.